From Scrolling to Awareness: How @zerowaste.id_officials Insta Campaign Shapes Gen Z Eco-Consciousness - Wanna Zahara; Febri Nurrahmi (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2024)
Awareness of the importance of environmental preservation can be effectively cultivated through social media. One example is the zero waste campaign that uses Instagram to reduce the use of single-use plastics. This study aims to analyze the influence of the zero waste campaign on the Instagram account @zerowaste.id_official on the environmental awareness of students at Syiah Kuala University. The study adopts Kotler's model, specifically the learn, feel, do model. The research method used is explanatory quantitative, with surveys distributed through Google Forms to 133 students at Syiah Kuala University who have seen content from the Instagram account @zerowaste.id_official. The sampling technique used is quota sampling from each faculty. The research results show that the t-value (5.534) is greater than the t-table value (1.657) with a coefficient of determination of 0.189, meaning the zero waste campaign influences students' environmental awareness by 18.9%. The linear regression result shows a value of b = 0.404 and a significance level of 0.000. In conclusion, the zero waste campaign on the Instagram account @zerowaste.id_official has a positive and significant impact on the environmental awareness of students at Syiah Kuala University. This indicates that the greater the exposure to the campaign, the higher the students' environmental awareness.Kesadaran akan pentingnya menjaga lingkungan dapat ditumbuhkan secara efektif melalui media sosial. Salah satunya adalah kampanye zero waste yang menggunakan Instagram untuk mengurangi penggunaan plastik sekali pakai. Penelitian ini bertujuan untuk menganalisis pengaruh kampanye zero waste di akun Instagram @zerowaste.id_official terhadap kesadaran lingkungan mahasiswa Universitas Syiah Kuala. Penelitian ini mengadopsi model Kotler, yakni the learn, feel, do model. Metode yang digunakan adalah kuantitatif eksplanatif dengan survei yang disebarkan melalui Google Form kepada 133 mahasiswa Universitas Syiah Kuala yang pernah melihat konten Instagram @zerowaste.id_official. Teknik sampling yang digunakan adalah quota sampling pada setiap fakultas. Hasil penelitian menunjukkan bahwa nilai thitung (5,534) lebih besar dari nilai ttabel (1,657) dengan koefisien determinasi 0,189, yang artinya kampanye zero waste mempengaruhi kesadaran lingkungan mahasiswa sebesar 18,9%. Hasil regresi linear menunjukkan nilai b = 0,404 dan taraf signifikansi 0,000. Kesimpulannya, kampanye zero waste di akun Instagram @zerowaste.id_official memiliki pengaruh positif dan signifikan terhadap kesadaran lingkungan mahasiswa Universitas Syiah Kuala. Ini menunjukkan bahwa semakin tinggi terpaan kampanye, semakin tinggi pula kesadaran lingkungan mereka.